Application of low‐cost, eco‐friendly adsorbents for the removal of dye contaminants from wastewater: Current developments and adsorption technology. Issue 1 (29th March 2022) - Laskar, Nirban; Kumar, Upendra
Abstract: The review study focuses on dye contamination of wastewater and adsorption approaches to achieve the lowest dye waste in wastewater discharge. The dyes require extensive use in several applications suited for commercial consumption, but the dyes are serious pollutants when dumped directly into water bodies without sufficient treatment. The review study briefly discusses the current methodologies carried out for the adsorption mechanism, the relevance of adsorption, and adsorption factors for the examined system. Langmuir and Freundlich isotherm models and a pseudosecond order kinetic model were found to properly represent dye uptake. To fully appreciate the molecular interactions between the adsorbent and adsorbate, additional study into theoretical dye adsorption modeling is necessary. As a low‐cost adsorbent for dye treatment and the manufacturing of activated carbon, agricultural waste material in both its natural and modified forms is explored in this review article for its dye adsorption capabilities. The adsorption behavior and mechanism may be better understood by employing operational parameters, kinetics, and isotherm models, as described in this article. The initial concentration, pH, and temperature all play a function in the adsorption process and are discussed in depth.